Presynaptic protein synaptotagmin1 regulates the activity‐induced remodeling of synaptic structures in cultured hippocampal neurons. Issue 7 (22nd April 2013) - Inoue, Yuriko; Takayanagi, Masaaki; Sugiyama, Hiroyuki
<x xml:space="preserve">Abstract</x> Activity‐dependent reorganizations of central neuronal synapses are thought to play important roles in learning and memory. Although the precise mechanisms of how neuronal activities modify synaptic connections in neurons remain to be clarified, the activity‐induced neuronal presynaptic proteins such as synaptotagmin1 may contribute to the onset of synaptic remodeling. To understand better the physiological roles of synaptotagmin1, we first examined the prolonged effects of neuronal stimulation capable of inducing synaptotagmin1 on the distribution of a postsynaptic proteins (PSD) protein Homer1c by immunostaining. Previously we found that glutamate stimulation induced other postsynaptic proteins, such as postsynaptic density‐95 (PSD95), a biphasic change with an initially diffuse distribution after 30 min to 1 hr, followed by reassembly to more than the original level after 4–8 hr, suggesting that glutamate stimulation induces a global biphasic alteration in synaptic structures. To dissect further the functions of synaptotagmin1 in the activity‐induced synaptic remodeling, short hairpin RNA (shRNA) vectors that specifically block the expression of endogenous synaptotagmin1 were constructed. When the shRNA of synaptotagmin1 was introduced to the neurons, the activity‐induced changes were almost completely suppressed. We found that synaptotagmin1 contributes to the postsynaptic remodeling in a retrograde manner. Our data indicate that synaptotagmin1 regulates the activity‐induced biphasic changes of post‐ and presynaptic sites. © 2013 Wiley Periodicals, Inc.